2013
DOI: 10.1167/13.2.24
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of perceptual rivalry in bistable and tristable perception

Abstract: Human observers are extremely adept at correctly interpreting the visual input that they receive despite its inherent ambiguity. There are, however, situations in which no single, valid interpretation exists and perception oscillates. Such situations offer insight into the processes underlying perception, as they reveal the conditions under which our percept can alter in the presence of an unchanging physical stimulus. Many studies have focused on perceptual switching during binocular and monocular rivalry, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
(89 reference statements)
4
15
0
Order By: Relevance
“…For other tristable stimuli, several observations made by Naber and colleagues (2010) and Wallis and Ringelhan (2013) after pooling data over several parameters showed some commonalities with our behavioral data and could be accounted for by our model with the aforementioned roles for noise and adaptation. For instance, Naber and colleagues (2010) reported that switch-back triplets typically have longer durations than average for the intermediate percept (in our case, C) and shorter durations than average for the first percept in the triplet (in our case, T 1 ).…”
Section: Parametric Manipulationssupporting
confidence: 81%
See 2 more Smart Citations
“…For other tristable stimuli, several observations made by Naber and colleagues (2010) and Wallis and Ringelhan (2013) after pooling data over several parameters showed some commonalities with our behavioral data and could be accounted for by our model with the aforementioned roles for noise and adaptation. For instance, Naber and colleagues (2010) reported that switch-back triplets typically have longer durations than average for the intermediate percept (in our case, C) and shorter durations than average for the first percept in the triplet (in our case, T 1 ).…”
Section: Parametric Manipulationssupporting
confidence: 81%
“…Although percept choice and percept switching may involve different processes (Noest, van Ee, Nijs, & van Wezel, 2007), these results suggest that a form of adaptation must be present in ambiguous visual perception. Moreover, recent results for other types of tristable visual stimuli also point in favor of an adaptation model to account for certain aspects of transitions and durations (Naber et al, 2010;Wallis & Ringelhan, 2013).…”
Section: Different Roles For Noise and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early versions of this hypothesis related perceptual reversals to neural fatigue or "satiation", and were formulated in the context of now-discredited Gestalt assumptions about the underlying physiology (Kohler & Wallach, 1944). Subsequent versions of the hypothesis have proposed that exposure to a reversible figure activates two or more mutually exclusive sets of neural structures that compete for dominance (e.g., Blake, Sobel, & Gilroy, 2003;Nawrot & Blake, 1989;Toppino & Long, 1987;Wallis & Ringelhan, 2013). Some aspect of the neural structures supporting the currently dominant percept is thought to adapt or weaken over time, until the structures underlying an alternate interpretation of the reversible stimulus gain ascendancy, producing a phenomenal reversal.…”
Section: Introductionmentioning
confidence: 99%
“…However, considerable caution should be exercised in generalizing the results and conclusions from one empirical domain to the other. Despite many similarities between the two sets of phenomena, there also are important differences (e.g., Meng & Tong, 2004;Wallis & Ringelhan, 2013). For example, many binocular rivalry effects can be traced to interocular competition, which clearly is not a factor in the perception of ambiguous stimuli (e.g., Lee & Blake, 1999;Tong, 2001;Tong & Engle, 2001).…”
Section: Introductionmentioning
confidence: 99%